Crafting a Fibre Scene in Cape Breton: The Tools, Technologies, and Motivations of the Unspun Heroes - Tulk, Janice Esther (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2018)
In the 21st century, spinning, knitting, and weaving are largely thought of as hobbies, pastimes, or small business activities. Despite the availability of mass-produced wool and fibre products, homespun and handmade products have seen a resurgence in popularity, partly because practitioner communities have developed. This article provides an ethnography of one such group, the Unspun Heroes in Cape Breton, Nova Scotia. Following a brief history of the group, the individually- and communally-owned tools and technology utilized within the Unspun Heroes is described. The forces that shape fibre artists’ access to tools and other resources of their craft in Cape Breton are identified, elucidating how strategies of shared, repurposed, and DIY tools enable fibre artists to sustainably engage in their craft. The motivations of members of the group are then considered, demonstrating how economic diversification strategies in Cape Breton have facilitated fibre arts, but are seldom the driving force for engagement in fibre arts and the Unspun Heroes group. In conclusion, the concept of “scene” is applied to the people, places, technologies, and connections described in this ethnography of the Unspun Heroes as a way of understanding the complex web of interactions and activities that plays out within and around the fluid membership of the group. This exploration demonstrates the innovative and entrepreneurial ethos of fibre artists in rural Canada.